A (in)visibilidade da violência contra a mulher em uma Unidade de Saúde da Família - Pereira, Larissa Angelo. [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Violence against women is a serious public health problem, the partners are the main perpetrators of violence. Thus, domestic violence situations are expected to be detected at the Family Health Unit, the main gateway to health services located in the territory where families live. The present study aimed to analyze the (non) detection of violence against the woman by intimate partner from the perceptions of the professionals of a Unit. It is a qualitative research, whose data collection was done through a focus group with six professionals belonging to the minimum team of the health unit. After the analysis of the focus group, three categories of analysis were highlighted: 1) the (non) identification of violence against women; 2) correlating violence against women with mental health demands; and 3) the lack of an articulated support network for women in situations of violence. The results have shown that there is difficulty in identifying cases of violence against women due to the care model adopted by the professionals, based on immediate actions direct to the physiological symptoms and disregarding the patriarchal societal order, besides not using the intersectoral network to face the problem.

A violência contra a mulher é um grave problema de saúde pública, os companheiros se configuram como principais perpetradores da violência. Assim, espera-se que as situações de violência doméstica sejam detectadas na Unidade de Saúde da Família, principal porta de entrada para os serviços de saúde localizada no território em que vivem as famílias. O presente estudo objetivou analisar a (não) detecção da violência contra a mulher por parceiro íntimo a partir das percepções dos profissionais de uma Unidade. Trata-se de uma pesquisa qualitativa, cuja coleta de dados se deu por meio de um grupo focal com seis profissionais pertencentes a equipe mínima da unidade de saúde. Após a análise do grupo focal, destacaram-se três categorias de análise: 1) a (não) identificação a violência contra a mulher; 2) correlacionando a violência contra a mulher com demanda de saúde mental; e 3) a falta de uma rede articulada de apoio às mulheres em situação de violência. Constatou-se que há dificuldade na identificação de casos de violência contra a mulher devido ao modelo de atenção adotado pelos profissionais, pautado em ações imediatistas voltadas para os sintomas fisiológicos e desconsidera a ordem societária patriarcal, além de não utilizar a rede intersetorial para enfrentamento do problema.
The (in) visibility of violence against women in a Family Health Unit
Keywords: Family health strategy; Violence against women; Domestic violence; Estratégia saúde da família; Violência contra a mulher; Violência familiar